Power-free plasma separation based on negative magnetophoresis for rapid biochemical analysis - Lin Zeng; Chao Liu; Yi Yang; Shi Hu; Ruihan Li; Xiaotian Tan; Jienan Shen; Yi Zhang; Shaohui Huang; Hui Yang (Microsystems & Nanoengineering)
Abstract We present a versatile platform for label-free magnetic separation of plasma, tailored to accommodate diverse environments. This innovative device utilizes an advanced long-short alternating double Halbach magnetic array, specifically engineered for optimal magnetic separation. The array’s adaptability allows for seamless integration with separation channels of varying sizes, enabling static separation of whole blood. The platform has a highly flexible processing throughput, spanning from 100 μL to 3 mL per separation cycle without sacrificing separation efficiency. A key aspect of this device is its power-free operation throughout the separation process, obviating the complexity of conventional separation devices. Its effectiveness is demonstrated by the extraction of 40 μL of plasma from 100 μL of rat whole blood within 8 min. The separated plasma proved effective for subsequent analysis of antibody concentration and size in the separated plasma for pharmacokinetic investigations, yielding results on par with those obtained via centrifugation. Furthermore, the device’s high-throughput capability was validated using human whole blood, achieving 3 mL of plasma separation in just 1 min. In a follow-up study on COVID-19 IgG antibody detection, the results matched those from centrifugation. The device demonstrates a separation efficiency of 99.9% for cells larger than 1 μm in both rat and human blood samples, with a plasma recovery rate of 72.7%. In summary, our magnetic separation device facilitates rapid plasma extraction from whole blood, with a capacity of up to 3 mL per minute in human blood, without compromising subsequent plasma-based analyses, thereby highlighting its broad applicability across diverse settings.